A novel intervention to enhance transoceanic fiber effectiveness through advanced QX 5252 CMOS driver - Elmutasim, Elsayed Imadeldin; Izzeldin Ibrahim, Mohamed Abdelaziz (Institute of Electrical and Electronics Engineers Inc., 2021)
Submarine fiber networks are considered the backbone of communication between countries, hence the operators expecting to get high quality and performance efficiency. Due to that, sea cable manufacturers ramping up the efforts to enhance the bandwidth availability, reliability, and entire performance satisfactory to the customers' demand because they well know laying out new transoceanic fiber is more expensive than other ground cables. On the other hand, separation of power cable from the fiber in the submarine system making the repair, troubleshooting, and even survey test likewise costly due to utilizing the different platforms, tools, and expertise to achieve the task. This paper undertakes an extensive test in fiber optic including submarine cable through give a spotlight to the attenuation elements such as reflection loss as well as the power cable standalone impact in the submarine fiber network. The investigation based on the real survey test which considers the cable from the beach manhole to the main station shelter and proposes to use an advanced QX5252 CMOS to incorporate, magnifying the voltage and power discharge depends on the system requirements. The advanced chip also able to sense the signal thus would occupy many aspects in addition to care for the earthing process via overload discharge. The scientific approach of the proposal assessed the potential solution to mitigate the challenges in the submarine cable as well as fiber optic.